If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2a + b = -16 Solving 2a + b = -16 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1b' to each side of the equation. 2a + b + -1b = -16 + -1b Combine like terms: b + -1b = 0 2a + 0 = -16 + -1b 2a = -16 + -1b Divide each side by '2'. a = -8 + -0.5b Simplifying a = -8 + -0.5b
| 5(-7x+3)=-265 | | 6n+3(8n+5)=255 | | 2xy-6y= | | 9y-2(y+14)=84 | | 5(13-9)-10(5+11x)=170 | | 3(7-8n)-4=-103 | | -18=8-6k-8 | | 4ab-5b= | | 6x-9y=25 | | 9x^2-4y^2-36x-24y+36=0 | | x^2+2.86x-21428.57=0 | | -41=x+88 | | Y=3x^2-9x+18 | | 2y-25=19 | | 0=-7x-2x | | Ax+7=bx+8 | | y-(-2)=8(x-(-2)) | | -7=.2+m | | A=mnp | | 5.8(x-4)=0.2x+6.8 | | 10-3y=7y+2 | | v-15=-24 | | (2+3x)=63 | | 10x*x=495 | | 3y+6=3+18 | | 2y-2=2y-22 | | (25*x)+(15*2)=30500 | | 100=1.1X | | 7(3+7n)=-25+3n | | (25*x)+(15*5)=30500 | | 9.95+0.03s=c | | 18n=-1008 |